A cement-based supercapacitor electrode material doped with pre-oxidized bismuth and a preparation method and application thereof

CN122950310APending Publication Date: 2026-10-20NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611087949.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]具体而言,这种被称为电化学水泥基储能复合材料(EC3)通常可以理解为一个由水泥基体、导电碳材料以及电解质体系共同构成的复杂电子导电水泥基储能系统,在该材料体系中,水泥水化产物构建了坚固的无机骨架以支撑结构,导电碳材料则交织形成高效的电子传输网络,二者在电解液的充分浸润下形成广阔的电化学储能界面;然而,现有的水泥基超级电容器技术主要依赖于碳材料的双电层储能机制,其电容贡献主要源于电解液离子在碳材料孔道和表面的物理吸附与脱附过程,尽管这种储能方式赋予了器件较好的循环稳定性,但其比电容的提升空间十分有限,难以满足日益增长的高能量密度需求

Benefits of technology

1.本发明通过引入具有核壳结构的预氧化铋,使电极兼具碳材料的双电层电容和铋基材料的赝电容。两种储能方式协同作用,相比仅依赖双电层电容的传统水泥基碳电极,比电容和能量密度得到大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of supercapacitor materials technology, specifically relating to a cement-based supercapacitor electrode material doped with pre-bismuth oxide, its preparation method, and its applications. By introducing pre-bismuth oxide with a core-shell structure, this invention enables the electrode to possess both the double-layer capacitance of carbon materials and the pseudocapacitance of bismuth-based materials. The synergistic effect of these two energy storage methods significantly improves specific capacitance and energy density compared to traditional cement-based carbon electrodes that rely solely on double-layer capacitance. The pre-bismuth oxide metal core of this invention ensures excellent local conductivity, effectively reducing the resistance to charge transport within the active material. Combined with the macroscopic conductive network constructed from carbon materials, the entire electrode exhibits low internal resistance, thus possessing excellent rate performance, i.e., maintaining high capacitance even at high current densities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of supercapacitor materials technology, specifically relating to a cement-based supercapacitor electrode material doped with pre-oxidized bismuth, its preparation method, and its application. Background Technology

[0002] With the transformation of the global energy structure and the rapid development of energy storage technology and building functional materials, the deep integration of traditional structural materials with advanced energy storage devices has gradually become a promising and important research direction in the field of materials science. Among the many building materials, cement-based materials have become an ideal matrix for constructing new functional materials due to their natural advantages such as low cost, wide availability, free casting and molding, and excellent mechanical stability. If conductive networks and electrochemically active components can be successfully introduced into the cement matrix through material design, it is expected that a cement-based supercapacitor with both the load-bearing function of traditional building materials and the high-efficiency energy storage function can be prepared, thereby realizing the integration of building structure and energy storage.

[0003] Specifically, this type of composite material called electrochemical cement-based energy storage (EC3) can generally be understood as a complex electronically conductive cement-based energy storage system composed of a cement matrix, conductive carbon materials, and an electrolyte system. In this material system, cement hydration products construct a robust inorganic framework to support the structure, while conductive carbon materials intertwine to form an efficient electron transport network. The two form a broad electrochemical energy storage interface under the full wetting of the electrolyte. However, existing cement-based supercapacitor technology mainly relies on the double-layer energy storage mechanism of carbon materials. Its capacitance contribution mainly comes from the physical adsorption and desorption process of electrolyte ions in the pores and surface of carbon materials. Although this energy storage method gives the device good cycle stability, its specific capacitance improvement space is very limited, making it difficult to meet the ever-increasing demand for high energy density.

[0004] Therefore, in order to overcome this bottleneck, developing a new type of cement-based supercapacitor EC3 that can maintain the excellent electrochemical activity of bismuth-based materials and effectively improve their electron transport efficiency and interfacial compatibility has become a key technical problem that urgently needs to be solved. This is of great scientific significance for promoting the practical application of structural energy storage materials. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a cement-based supercapacitor electrode material doped with pre-oxidized bismuth. This material can introduce a bismuth-based redox pseudocapacitive reaction while maintaining the mechanical stability and formability of the cement-based material. At the same time, conductive carbon material constructs an electron transport channel, and the cement hydration pore structure provides an ion transport path, thereby improving the specific capacitance, rate performance, and cycle stability of the cement-based supercapacitor.

[0006] The above-mentioned objective of the present invention is achieved by the following scheme: A cement-based supercapacitor electrode material doped with pre-bismuth oxide, the electrode material comprising a cement matrix, a conductive carbon material, and pre-bismuth oxide particles; The pre-oxidized bismuth particles have a metallic bismuth core and a bismuth oxide active layer covering the surface of the metallic bismuth core; The conductive carbon material forms a three-dimensional conductive network in the electrode material, and the pre-oxidized bismuth particles are dispersed in the porous structure formed by the three-dimensional conductive network and the cement matrix.

[0007] In the above-mentioned cement-based supercapacitor electrode material, the electrode material comprises the following raw materials in parts by weight: 70-90 parts cement, 5-20 parts conductive carbon material, and 1-10 parts pre-oxidized bismuth particles.

[0008] In the above-mentioned cement-based supercapacitor electrode material, the pre-oxidized bismuth particles are obtained by heat-treating metallic bismuth powder in air at 120-260°C for 0.5-6 hours.

[0009] In the above-mentioned cement-based supercapacitor electrode materials, the average particle size of the pre-oxidized bismuth particles is 50nm-50μm.

[0010] Preferably, the pre-oxidized bismuth particles have an average particle size of 1-20 μm.

[0011] The bismuth core of this invention serves as the conductive core, ensuring excellent electronic conductivity within the particles. In electrochemical reactions, it acts as a highly efficient "electron highway," rapidly collecting or transporting electrons to the active layer on the particle surface, thereby significantly reducing charge transfer resistance. The bismuth oxide active layer, acting as the functional shell, provides abundant Faraday pseudocapacitive reaction sites. This oxide layer undergoes rapid and reversible surface redox reactions in the electrolyte, contributing a pseudocapacitance far exceeding that of the double-layer capacitance. Simultaneously, the oxide layer surface typically exhibits better hydrophilicity, facilitating electrolyte wetting and ensuring ions can smoothly reach the reaction interface. Through this "internal conductivity and external activity," the pre-oxidized bismuth particles of this invention synergistically resolve the inherent contradiction between insufficient activity of metallic bismuth and poor conductivity of bismuth oxide, achieving a balance between electrochemical activity and electronic conductivity.

[0012] In the above-mentioned cement-based supercapacitor electrode materials, the conductive carbon material includes at least one of porous carbon material for providing double-layer capacitance and conductive agent for constructing a conductive network; wherein the porous carbon material is at least one of activated carbon and porous graphene; and the conductive agent is at least one of conductive carbon black, Ketjen black, carbon nanotubes and acetylene black.

[0013] The present invention also provides a method for preparing the above-mentioned electrode material, the method comprising the following steps: S1: Mix cement, conductive carbon material and pre-oxidized bismuth particles to obtain dry-mixed powder; S2: Add water to the dry-mixed powder and stir to form a formable slurry; S3: The formable slurry is formed into a blank of a predetermined shape; S4: The blank is subjected to hydration curing and drying treatment to obtain the electrode material.

[0014] In the above preparation method, the mass ratio of water to cement is (0.3-2.0):1.

[0015] In the above preparation method, in step S4, the temperature for hydration curing is 20-40℃, the relative humidity is 60-80%, and the curing time is 1-14 days.

[0016] The present invention also provides a cement-based supercapacitor, comprising a current collector, a positive electrode, a negative electrode, a separator, and an electrolyte; wherein the positive electrode and the negative electrode are disposed on both sides of the separator, and the outer surfaces of the positive electrode and the negative electrode are covered with a current collector, and the positive electrode and / or the negative electrode adopts the electrode material as described in any one of claims 1-5.

[0017] The present invention also provides an application of the above-mentioned electrode material in structural energy storage integrated building materials, building energy storage components, embedded energy storage units or cement-based electrochemical energy storage devices.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention introduces pre-oxidized bismuth with a core-shell structure, enabling the electrode to possess both the double-layer capacitance of carbon materials and the pseudocapacitance of bismuth-based materials. The synergistic effect of these two energy storage methods significantly improves specific capacitance and energy density compared to traditional cement-based carbon electrodes that rely solely on double-layer capacitance.

[0019] 2. The pre-oxidized bismuth metal core of this invention ensures excellent local conductivity, effectively reducing the resistance to charge transport within the active material. Combined with the macroscopic conductive network constructed from carbon materials, the entire electrode exhibits low internal resistance, thus possessing excellent rate performance, i.e., maintaining high capacitance even at high current densities.

[0020] 3. Compared to pure metallic bismuth, the oxide layer on the surface of the pre-oxidized bismuth of this invention exhibits better interfacial compatibility with cement hydration products and aqueous electrolytes, which facilitates its uniform dispersion in cement slurry and thorough wetting with the electrolyte. Simultaneously, the cement stone network formed by hydration firmly fixes the active particles in situ, effectively inhibiting their aggregation or detachment during long-term cycling, thus ensuring excellent cycling stability.

[0021] 4. The electrode material of this invention uses cement as a matrix. While providing energy storage function, it inherits the mechanical load-bearing capacity, castability, and low cost advantages of cement materials, making it possible to develop integrated energy storage building components such as load-bearing and fireproof walls and floors.

[0022] 5. The core pre-oxidized bismuth active material of this invention can be prepared through a simple one-step heat treatment, without the need for complex and expensive equipment or harsh reaction conditions. Subsequent composite processes with cement and carbon materials are compatible with traditional concrete preparation processes, are low-cost, and easily scalable for large-scale production. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the overall structure and a flowchart of the preparation process of the cement-based supercapacitor with pre-oxidized bismuth added according to the present invention.

[0024] Figure 2 This is a schematic diagram of the structure of the pre-oxidized bismuth particles in Embodiment 1 of the present invention.

[0025] Figure 3 This is a schematic diagram of the capacitor energy storage mechanism in Embodiment 1 of the present invention.

[0026] Figure 4 This is a schematic diagram comparing the cyclic voltammetry curves of capacitors with different pre-oxidized bismuth contents in Examples 1-4 of the present invention.

[0027] Figure 5 This is a schematic diagram comparing the electrochemical impedance spectra of capacitors with different pre-oxidized bismuth contents in Examples 1-4 of the present invention. Detailed Implementation

[0028] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0029] Raw material description: Cement: PO 42.5 ordinary Portland cement.

[0030] Bismuth metal powder: analytical grade, particle size approximately 10 μm.

[0031] Activated carbon (AC): specific surface area 1500 m² / g.

[0032] Ketjen Black (KB): Conductive carbon black.

[0033] Electrolyte: 1 mol / L KCl aqueous solution.

[0034] Example 1:

[0035] according to Figure 1 The process shown is used to prepare the cement-based supercapacitor EC3: S1. The preparation of pre-oxidized bismuth particles includes the following steps: Weigh metallic bismuth powder, spread it evenly in a ceramic boat, and then place it in a muffle furnace. Under an air atmosphere, heat to 200℃ at a heating rate of 3℃ / min and hold for 2 h. After heat treatment, allow it to cool naturally to room temperature, remove it, and gently grind it to obtain a structure as shown. Figure 2 The pre-oxidized bismuth powder shown is characterized by a bismuth oxide-containing oxide layer forming on its surface, while retaining the metallic bismuth phase internally. Its structure can be represented as Bi / BiOx composite particles, where BiOx represents bismuth oxide, bismuth hydroxyoxylate, or other bismuth species containing oxidized states.

[0036] S2. Prepare the raw materials according to the following mass proportions: 85 parts ordinary silicate cement, 5 parts activated carbon, 5 parts Ketjen black, and 5 parts pre-oxidized bismuth. S3. Place activated carbon, Ketjen black and pre-oxidized bismuth in a mixer and mix thoroughly to ensure that the pre-oxidized bismuth is evenly dispersed in the carbon material system. Then add ordinary silicate cement and continue mixing to obtain dry-mixed powder. S4. Add deionized water to the dry-mixed powder, and control the mass ratio of deionized water to cement to be 1.4:1. Stir to form a uniform cement-based conductive energy storage slurry. In this slurry, activated carbon mainly provides double-layer energy storage sites, Ketjen black mainly constructs the conductive network, pre-oxidized bismuth mainly provides pseudocapacitive activity, and cement forms a supporting framework during the subsequent hydration process.

[0037] S5. Pour cement-based conductive energy storage slurry into a mold, and scrape it onto the surface of the foamed nickel current collector to form a first cement-based composite energy storage layer. Then, lay a glass fiber membrane impregnated with electrolyte on the surface of the first cement-based composite energy storage layer, and continue to scrape a second cement-based composite energy storage layer on top of the glass fiber membrane impregnated with electrolyte. Finally, set a foamed nickel current collector on the outside of the second cement-based composite energy storage layer. S6. Then, it is hydrated and cured for 7 days at 30℃ and 65% relative humidity, and finally dried to obtain cement-based supercapacitor EC3.

[0038] Figure 3This is a schematic diagram of the capacitor energy storage mechanism in Embodiment 1 of the present invention. As shown in the diagram, cement hydration products form a continuous inorganic framework in EC3, providing structural support and pore channels for the electrodes; activated carbon particles provide a large specific surface area and double-layer energy storage sites; Ketjenblack particles overlap and connect activated carbon and pre-oxidized bismuth particles, forming a three-dimensional electron transport network; the BiOx active layer on the surface of the pre-oxidized bismuth particles undergoes a reversible redox reaction during charging and discharging, providing additional pseudocapacitance, while the internal metallic bismuth phase helps reduce the particle's own electron transport resistance. Thus, a synergistic energy storage mechanism of "structural support-electron transport-ion diffusion-pseudocapacitive reaction" is formed between the cement matrix, the conductive carbon network, and the pre-oxidized bismuth particles, thereby improving the specific capacitance, energy density, and rate performance of EC3.

[0039] Example 2:

[0040] S1. The preparation of pre-oxidized bismuth particles includes the following steps: Weigh metallic bismuth powder, spread it evenly in a ceramic boat, and then place it in a muffle furnace. Under an air atmosphere, heat to 200℃ at a heating rate of 3℃ / min and hold for 2 h. After heat treatment, allow it to cool naturally to room temperature, remove it, and gently grind it to obtain pre-oxidized bismuth powder. The surface of the pre-oxidized bismuth powder forms an oxide layer containing bismuth oxide, while the interior retains the metallic bismuth phase. Its structure can be represented as Bi / BiOx composite particles, where BiOx represents bismuth oxide, bismuth hydroxyoxylate, or other bismuth species containing oxidized states.

[0041] S2. Prepare the raw materials according to the following mass proportions: 90 parts ordinary silicate cement, 5 parts activated carbon, 5 parts Ketjen black, and 0 parts pre-oxidized bismuth. S3. Place activated carbon, Ketjen black and pre-oxidized bismuth in a mixer and mix thoroughly to ensure that the pre-oxidized bismuth is evenly dispersed in the carbon material system. Then add ordinary silicate cement and continue mixing to obtain dry-mixed powder. S4. Add deionized water to the dry-mixed powder, and control the mass ratio of deionized water to cement to be 1.4:1. Stir to form a uniform cement-based conductive energy storage slurry. In this slurry, activated carbon mainly provides double-layer energy storage sites, Ketjen black mainly constructs the conductive network, pre-oxidized bismuth mainly provides pseudocapacitive activity, and cement forms a supporting framework during the subsequent hydration process.

[0042] S5. Pour cement-based conductive energy storage slurry into a mold, and scrape it onto the surface of the foamed nickel current collector to form a first cement-based composite energy storage layer. Then, lay a glass fiber membrane impregnated with electrolyte on the surface of the first cement-based composite energy storage layer, and continue to scrape a second cement-based composite energy storage layer on top of the glass fiber membrane impregnated with electrolyte. Finally, set a foamed nickel current collector on the outside of the second cement-based composite energy storage layer. S6. Then, it is hydrated and cured for 7 days at 30℃ and 65% relative humidity, and finally dried to obtain cement-based supercapacitor EC3.

[0043] Example 3

[0044] S1. The preparation of pre-oxidized bismuth particles includes the following steps: Weigh metallic bismuth powder, spread it evenly in a ceramic boat, and then place it in a muffle furnace. Under an air atmosphere, heat to 200℃ at a heating rate of 3℃ / min and hold for 2 h. After heat treatment, allow it to cool naturally to room temperature, remove it, and gently grind it to obtain pre-oxidized bismuth powder. The surface of the pre-oxidized bismuth powder forms an oxide layer containing bismuth oxide, while the interior retains the metallic bismuth phase. Its structure can be represented as Bi / BiOx composite particles, where BiOx represents bismuth oxide, bismuth hydroxyoxylate, or other bismuth species containing oxidized states.

[0045] S2. Prepare the raw materials according to the following mass proportions: 87 parts ordinary silicate cement, 5 parts activated carbon, 5 parts Ketjen black, and 3 parts pre-oxidized bismuth. S3. Place activated carbon, Ketjen black and pre-oxidized bismuth in a mixer and mix thoroughly to ensure that the pre-oxidized bismuth is evenly dispersed in the carbon material system. Then add ordinary silicate cement and continue mixing to obtain dry-mixed powder. S4. Add deionized water to the dry-mixed powder, and control the mass ratio of deionized water to cement to be 1.4:1. Stir to form a uniform cement-based conductive energy storage slurry. In this slurry, activated carbon mainly provides double-layer energy storage sites, Ketjen black mainly constructs the conductive network, pre-oxidized bismuth mainly provides pseudocapacitive activity, and cement forms a supporting framework during the subsequent hydration process.

[0046] S5. Pour cement-based conductive energy storage slurry into a mold, and scrape it onto the surface of the foamed nickel current collector to form a first cement-based composite energy storage layer. Then, lay a glass fiber membrane impregnated with electrolyte on the surface of the first cement-based composite energy storage layer, and continue to scrape a second cement-based composite energy storage layer on top of the glass fiber membrane impregnated with electrolyte. Finally, set a foamed nickel current collector on the outside of the second cement-based composite energy storage layer. S6. Then, it is hydrated and cured for 7 days at 30℃ and 65% relative humidity, and finally dried to obtain cement-based supercapacitor EC3.

[0047] Example 4:

[0048] S1. The preparation of pre-oxidized bismuth particles includes the following steps: Weigh metallic bismuth powder, spread it evenly in a ceramic boat, and then place it in a muffle furnace. Under an air atmosphere, heat to 200℃ at a heating rate of 3℃ / min and hold for 2 h. After heat treatment, allow it to cool naturally to room temperature, remove it, and gently grind it to obtain pre-oxidized bismuth powder. The surface of the pre-oxidized bismuth powder forms an oxide layer containing bismuth oxide, while the interior retains the metallic bismuth phase. Its structure can be represented as Bi / BiOx composite particles, where BiOx represents bismuth oxide, bismuth hydroxyoxylate, or other bismuth species containing oxidized states.

[0049] S2. Prepare the raw materials according to the following mass proportions: 80 parts ordinary silicate cement, 5 parts activated carbon, 5 parts Ketjen black, and 10 parts pre-oxidized bismuth. S3. Place activated carbon, Ketjen black and pre-oxidized bismuth in a mixer and mix thoroughly to ensure that the pre-oxidized bismuth is evenly dispersed in the carbon material system. Then add ordinary silicate cement and continue mixing to obtain dry-mixed powder. S4. Add deionized water to the dry-mixed powder, and control the mass ratio of deionized water to cement to be 1.4:1. Stir to form a uniform cement-based conductive energy storage slurry. In this slurry, activated carbon mainly provides double-layer energy storage sites, Ketjen black mainly constructs the conductive network, pre-oxidized bismuth mainly provides pseudocapacitive activity, and cement forms a supporting framework during the subsequent hydration process.

[0050] S5. Pour cement-based conductive energy storage slurry into a mold, and scrape it onto the surface of the foamed nickel current collector to form a first cement-based composite energy storage layer. Then, lay a glass fiber membrane impregnated with electrolyte on the surface of the first cement-based composite energy storage layer, and continue to scrape a second cement-based composite energy storage layer on top of the glass fiber membrane impregnated with electrolyte. Finally, set a foamed nickel current collector on the outside of the second cement-based composite energy storage layer. S6. Then, it is hydrated and cured for 7 days at 30℃ and 65% relative humidity, and finally dried to obtain cement-based supercapacitor EC3.

[0051] Example 5:

[0052] The difference from Example 1 is that, in step S1, the preparation of the pre-oxidized bismuth particles includes the following steps: heating to 120°C at a heating rate of 3°C / min and holding at that temperature for 2 h.

[0053] Example 6:

[0054] The difference from Example 1 is that, in step S1, the preparation of the pre-oxidized bismuth particles includes the following steps: heating to 160°C at a heating rate of 3°C / min and holding at that temperature for 2 h.

[0055] Example 7:

[0056] The difference from Example 1 is that, in step S1, the preparation of the pre-oxidized bismuth particles includes the following steps: heating to 240°C at a heating rate of 3°C / min and holding at that temperature for 2 h.

[0057] Example 8:

[0058] The difference from Example 1 is that, in step S1, the preparation of the pre-oxidized bismuth particles includes the following steps: heating to 260°C at a heating rate of 3°C / min and holding at that temperature for 2 h.

[0059] Comparative Example 1: The only difference from Example 1 is that the pre-oxidized bismuth particles are replaced with metallic bismuth powder.

[0060] Comparative Example 2: The only difference from Example 1 is that the pre-oxidized bismuth particles are replaced with bismuth oxide powder.

[0061] The testing method is as follows: The EC3 samples prepared in Examples 1-8 and Comparative Examples 1-2 were subjected to electrochemical performance tests under the same conditions. Before the test, the samples were thoroughly immersed in a 1 mol / L KCl aqueous solution to allow the electrolyte to penetrate the cement-based pores and the interior of the membrane. The test voltage window was set to 0-1.0 V.

[0062] Cyclic voltammetry tests were performed using an electrochemical workstation at scan rates of 5, 10, 20, 50, and 100 mV / s to compare the electrochemical response area and pseudocapacitive characteristics of different samples. Constant current charge-discharge tests were conducted at current densities of 0.02, 0.05, 0.1, 0.2, and 0.5 A / g. The energy density and power density were preferably calculated based on the discharge curve at 0.05 A / g to better reflect the actual low-power output characteristics of cement-based energy storage devices.

[0063] The specific capacitance is calculated using the formula C = I × Δt / (m × ΔV), where I is the discharge current, Δt is the discharge time, m is the total mass of the cement-based composite electrodes on both sides of EC3, and ΔV is the effective discharge voltage after deducting the IR drop. The energy density is calculated using the formula E = 0.5 × C × (ΔV)^2 / 3.6, and the power density is calculated using the formula P = 3600 × E / Δt. Both energy and power densities are calculated based on the overall mass of the cement-based composite electrode, not just the mass of the carbon material or bismuth-based active component.

[0064] Capacity retention was obtained through cycle stability testing, involving 5000 consecutive charge-discharge cycles at a current density of 1 A / g. The capacity retention was calculated as the ratio of the specific capacitance at the 5000th cycle to the initial specific capacitance. Electrochemical impedance spectroscopy was performed in the frequency range of 100 kHz–0.01 Hz with a perturbation voltage amplitude of 5 mV to analyze equivalent series resistance, interfacial charge transfer impedance, and ion diffusion behavior.

[0065] Table 1: Performance test results of supercapacitors prepared in the examples and comparative examples

[0066] As shown in Table 1, Example 1 exhibited the best overall performance when pre-oxidized at 200℃ for 2 hours with a pre-oxidized bismuth content of 5 parts, achieving a capacity retention rate of 88.7%, an energy density of 0.82 Wh / kg based on the overall mass of the cement-based composite electrode, and a power density of 24.6 W / kg. Compared to Example 2 without pre-oxidized bismuth, Example 1 showed significantly improved energy and power densities. Compared to Comparative Example 1, which directly added metallic bismuth powder, and Comparative Example 2, which directly added bismuth oxide powder, Example 1 simultaneously demonstrated higher capacity retention, energy density, and power density, indicating that the pre-oxidized bismuth core and bismuth oxide active layer can achieve a synergistic improvement in conductivity and pseudocapacitive activity.

[0067] Figure 4-5 The figures show a comparison of EC3 cyclic voltammetry curves and electrochemical impedance spectroscopy (EIS) spectra under different pre-bismuth oxide contents in Examples 1-4 of this invention. As can be seen from the figures, compared to the sample without pre-bismuth oxide, the EC3 sample with an appropriate amount of pre-bismuth oxide exhibits a larger integrated area in the cyclic voltammetry curve, a longer discharge time in the constant current charge-discharge curve, and a lower equivalent series resistance and smaller interfacial impedance in the EIS. When the pre-bismuth oxide content is too low, the pseudocapacitive contribution is limited; when the pre-bismuth oxide content is too high, it leads to a decrease in the proportion of carbon materials, pore blockage, or particle agglomeration, thereby affecting electron transport and ion diffusion.

[0068] As can be seen from Examples 5-8, when the pre-oxidation temperature is too low, the surface oxidation of bismuth powder is insufficient, resulting in weak pseudocapacitive activity; when the pre-oxidation temperature is too high, the oxide layer is too thick or the particles agglomerate, which may lead to an increase in electron transport resistance.

[0069] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

[0070] Although the present invention has been described in detail and specific embodiments have been cited, it will be apparent to those skilled in the art that various changes or modifications can be made without departing from the spirit and scope of the invention.

Claims

1. A cement-based supercapacitor electrode material doped with pre-bismuth oxide, characterized in that, The electrode material includes a cement matrix, conductive carbon material, and pre-oxidized bismuth particles; The pre-oxidized bismuth particles have a metallic bismuth core and a bismuth oxide active layer covering the surface of the metallic bismuth core; The conductive carbon material forms a three-dimensional conductive network in the electrode material, and the pre-oxidized bismuth particles are dispersed in the porous structure formed by the three-dimensional conductive network and the cement matrix.

2. The cement-based supercapacitor electrode material according to claim 1, characterized in that, The electrode material comprises the following raw materials in parts by weight: 70-90 parts cement, 5-20 parts conductive carbon material, and 1-10 parts pre-oxidized bismuth particles.

3. The cement-based supercapacitor electrode material according to claim 1, characterized in that, The pre-oxidized bismuth particles are obtained by heat-treating metallic bismuth powder in air at 120-260°C for 0.5-6 hours.

4. The cement-based supercapacitor electrode material according to claim 1, characterized in that, The average particle size of the pre-oxidized bismuth particles is 50 nm-50 μm.

5. The cement-based supercapacitor electrode material according to claim 1, characterized in that, The conductive carbon material includes at least one of a porous carbon material for providing double-layer capacitance and a conductive agent for constructing a conductive network; wherein the porous carbon material is at least one of activated carbon and porous graphene; and the conductive agent is at least one of conductive carbon black, Ketjen black, carbon nanotubes and acetylene black.

6. A method for preparing the electrode material according to any one of claims 1-5, characterized in that, The method includes the following steps: S1: Mix cement, conductive carbon material and pre-oxidized bismuth particles to obtain dry-mixed powder; S2: Add water to the dry-mixed powder and stir to form a formable slurry; S3: The formable slurry is formed into a blank of a predetermined shape; S4: The blank is subjected to hydration curing and drying treatment to obtain the electrode material.

7. The preparation method according to claim 6, characterized in that, The mass ratio of water to cement is (0.3-2.0):

1.

8. The preparation method according to claim 6, characterized in that, In step S4, the temperature for hydration curing is 20-40℃, the relative humidity is 60-80%, and the curing time is 1-14 days.

9. A cement-based supercapacitor, characterized in that, It includes a current collector, a positive electrode, a negative electrode, a separator, and an electrolyte; wherein the positive electrode and the negative electrode are disposed on both sides of the separator, and the outer surfaces of the positive electrode and the negative electrode are covered with a current collector, and the positive electrode and / or the negative electrode are made of the electrode material as described in any one of claims 1-5.

10. The application of an electrode material as described in any one of claims 1-5 in structural energy storage integrated building materials, building energy storage components, embedded energy storage units, or cement-based electrochemical energy storage devices.